2018
DOI: 10.1073/pnas.1805572115
|View full text |Cite
|
Sign up to set email alerts
|

Memory-related hippocampal activation in the sleeping toddler

Abstract: Nonhuman research has implicated developmental processes within the hippocampus in the emergence and early development of episodic memory, but methodological challenges have hindered assessments of this possibility in humans. Here, we delivered a previously learned song and a novel song to 2-year-old toddlers during natural nocturnal sleep and, using functional magnetic resonance imaging, found that hippocampal activation was stronger for the learned song compared with the novel song. This was true regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
(46 reference statements)
0
30
0
1
Order By: Relevance
“…Several labs have avoided some of these constraints by performing fMRI experiments with infants or toddlers who are sedated 7 or sleeping 8 10 . These studies have found innovative ways to investigate aspects of early cognitive development, such as by cuing previously learned episodes during sleep 9 . There are also now several large-scale projects that seek to understand functional brain development in infants during rest (HEALthy Brain and Child Development Study, UNC/UMN Baby Connectome project 11 and Developmental Human Connectome Project).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several labs have avoided some of these constraints by performing fMRI experiments with infants or toddlers who are sedated 7 or sleeping 8 10 . These studies have found innovative ways to investigate aspects of early cognitive development, such as by cuing previously learned episodes during sleep 9 . There are also now several large-scale projects that seek to understand functional brain development in infants during rest (HEALthy Brain and Child Development Study, UNC/UMN Baby Connectome project 11 and Developmental Human Connectome Project).…”
Section: Introductionmentioning
confidence: 99%
“…There are many challenges to collecting fMRI data from infants: head and body motion, limited attention span, fussiness, inability to understand or follow instructions, high acoustic noise levels, and a lack of analysis approaches optimized for the infant brain. Several labs have avoided some of these constraints by performing fMRI experiments with infants or toddlers who are sedated 7 or sleeping [8][9][10] . These studies have found innovative ways to investigate aspects of early cognitive development, such as by cuing previously learned episodes during sleep 9 .…”
mentioning
confidence: 99%
“…The fMRI data included in this age range extend knowledge about global cortical and subcortical hemodynamic responses to musical stimuli. Prabhakar et al ( 2018 ) described increased bilateral hippocampi activation in sleeping toddlers, in response to a previously heard lullaby. This result indicates that music stimulates sub-cortical memory substrates in young children (Prabhakar et al, 2018 ).…”
Section: The Neurophysiological Processing Of Music In Childrenmentioning
confidence: 99%
“…Prabhakar et al ( 2018 ) described increased bilateral hippocampi activation in sleeping toddlers, in response to a previously heard lullaby. This result indicates that music stimulates sub-cortical memory substrates in young children (Prabhakar et al, 2018 ). In slightly older children, activation of the bilateral temporal lobes, frontal lobes, fusiform, and cerebellum were reported in response to music (Overy et al, 2004 ; Guerrero Arenas et al, 2016 ).…”
Section: The Neurophysiological Processing Of Music In Childrenmentioning
confidence: 99%
“…There are many challenges to collecting fMRI data from infants: head and body motion, limited attention span and fussiness, inability to understand or follow instructions, high acoustic noise levels, and a lack of analysis approaches optimized for the infant brain. Several labs have performed fMRI experiments with infants who are sedated 7 or sleeping [8][9][10] . However, there have been only a handful of successes when infants are awake and behaving during cognitive tasks [11][12][13] .…”
mentioning
confidence: 99%